PENGOBATAN TRADISIONAL MASYARAKAT DESA LUBUK AMBACANG KECAMATAN HULU KUANTAN KABUPATAEN KUANTAN SINGINGI - Randa, Gusti; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Research on traditional medicine was conducted in the village of Lubuk Ambacang District of Hulu Kuantan Kuantan District Singingi. This research was conducted with the aim to explain how the belief systems that underlie the use of traditional medicine in the village of Lubuk Ambacang society and how the effective use of traditional medicine in the view of people in Desa Lubuk Ambacang. In this study the author uses qualitative research, is an attempt to present the social world, and perspective in life, in terms of concept, behavior, perception, and the question of human investigate. Data collection techniques using observation, interview and documentation. The research proves that became the foundations of society in the use of traditional herbs that is based on faith (Religion), hereditary tradition as well as fact-based reality has been perceived. While the effectiveness of the use of traditional herbs in the village of Lubuk Ambacang society there are positive that in the field of health, the economy and maintain the tradition of hereditary. There is also a negative effectiveness, such as a distorted belief, believe that the shaman could cure diseases suffered by the patient.Keywords: Traditional medicine, Belief System, Effectiveness